John Scarborough will - Scarborough, John, active 1696.
Will (1696), annotated at a later date, of Scarborough, an ancestor of Herbert Hoover.
Blacksmith, of London, England.
Negative photocopy.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hoover, Herbert, -- 1874-1964 -- Family; Wills -- England -- London; Blacksmiths